Prevalence of methicillin resistant staphylococcus aureus and its SCCmec type among students at a private dental college hospital in Chennai - Vinshia, Jebadass Jasmine; Padmavathy, Kesavaram; Sathyapriya, Baskaran; Sudha, Jimson (Creative Pharma Assent, 2023)
Background: Since asymptomatic nasal carriage of Methicillin-resistant S. aureus (MRSA) is on the rise among healthcare professionals (HCPs), their prompt detection and decolonization would substantially decrease disease transmission. The study's primary goal was to identify MRSA nasal carriers among dental students/CRIs and determine their SCCmec type and their susceptibility to mupirocin. Methods: Anterior nasal swabs from 102 healthy dental students/ CRIs were collected aseptically and subjected to standard microbiological testing. The antibiotic susceptibility pattern of the S. aureus isolates was determined by Kirby Bauer disc diffusion method and mecA-mediated oxacillin (methicillin) resistance was determined using the cefoxitin disc method. PCR analysis of MRSA isolates determined the presence of mecA and their SCCmec types. D test deduced inducible clindamycin resistance. Results: Of the 102 participants screened, only 8(7.8%) carried S. aureus. Antibiotic susceptibility testing revealed that 5/8(62.5%) were MRSA isolates. Of which, only 2 MRSA isolates harbored mecA, and both belonged to the SCCmec type V. All S. aureus isolates were sensitive to Vancomycin, teicoplanin, and tigecycline when tested using agar screening method while 2/8 (25%) of the S. aureus isolates were D test positive and belonged to iMLSB phenotype. Conclusion: MRSA nasal carriers amongst HCWs/dental students are a cause of concern as they are a significant reservoir for transmission of MRSA among their co-workers as well as the community. Our results signify the need for screening for MRSA carriage and decolonization with mupirocin to substantially decrease the transmission of MRSA among dental students/patients.